Diagnostic potential of automated tractography in progressive supranuclear palsy variants - Potrusil, Thomas; Krismer, Florian; Beliveau, Vincent; Seppi, Klaus; Müller, Christoph; Troger, Felix; Göbel, Georg; Steiger, Ruth; Gizewski, Elke R.; Poewe, Werner; Scherfler, Christoph (Parkinsonism & related disorders, 2020)
Microstructural white matter integrity captured by diffusion-tensor imaging (DTI) is significantly more affected in progressive supranuclear palsy-Richardson's syndrome (PSP-RS) compared to PSP-parkinsonism (PSP–P). To characterize the microstructural integrity of large fascicular bundles using standardized probabilistic tractography and combine it with previously established DTI- and volumetric measures of subcortical brain structures in order to evaluate its diagnostic properties for the differentiation of PSP- RS, PSP-P and Parkinson's disease (PD). DTI metrics as well as volumes of subcortical brain regions, acquired by 3T MRI of patients with PSP-RS (n = 15), PSP-P (n = 13), and a mean disease duration of 2.7 ± 1.8 years, were quantified by probabilistic tractography as well as a validated infratentorial atlas and compared to PD (n = 18) and healthy controls (n = 20). Classification accuracy of MRI measures was tested by consecutive linear discriminant analyses. DTI metrics of the anterior thalamic radiation, the corticospinal tract, the superior longitudinal fasciculus, the bundles of the corpus callosum and cingulate, the dentatorubrothalamic tract as well as volumes of the dorsal midbrain, globus pallidus and thalamus were significantly altered in PSP-RS and to a lesser extent in PSP-P compared to PD and healthy controls. Linear discriminant analysis identified DTI metrics of the dentatorubrothalamic tract and the anterior thalamic radiation as well as the volume of the dorsal midbrain to classify correctly 91.3% of PSP-RS, PSP-P and PD patients. Observer-independent investigations of microstructural integrity of major fiber bundles improved existing MRI processing strategies to differentiate PSP-P from PSP-RS and PD, in their early disease stages. •Automated probabilistic tractography was applied to cohorts of PSP-RS, PSP-P and PD.•Probabilistic tractography revealed microstructural alterations of fiber bundles in PSP.•PSP-RS demonstrated more pronounced DTI changes of fiber tracts comparted to PSP-P•DTI of thalamic radiation and dentatorubrothalamic tract improved diagnostic accuracy of PSP variants.